Normative data of modified romberg balance test for risk of fall in elderly population from Pakistan - Sania Zahra,; Misbah Waris,; Qurat ul Ain,; Yasha Sajjad, (Journal of the Pakistan Medical Association, 2023)
Objective: To generate normative data of modified romberg balance test for the risk of fall among the elderly. Method: The crossectional study was conducted from July 1 to December 31, 2021, and comprised healthy adults of either gender aged 60 years and above from different cities of Pakistan. The participants were screened for balance issues using the Patient Reported Outcomes Measurement Information System Global Health Questionnaire. All th eindividuals were subjected to the modified romberg balance test. Data was analysed using SPSS 21. Results: Of the 2004 participants, 1,041(51.95%) were males and 963(48.05%) were females. The overall mean age was 70.36+6.20 years and mean body mass index was 21.92+3.08kg/m2. Overall, 207(10.33%) participants passed all the 4 conditions of the modified romberg balance test. Conclusion: With increasing age, the capability to perform modified romberg balance test decreased, increasing the chance of fall among the elderly. Key Words: Adult, Balance, Fall, Frail older, Musculoskeletal equilibrium.